TRANSFORMASI KEBIJAKAN DAN REGULASI KOMUNIKASI SIARAN TV ANALOG KE DIGITAL DI INDONESIA - Hasan, Kamaruddin; Sazali, Hasan (FISIP Universitas Malikussaleh, 2025)
Equitable distribution of information development in Indonesia aims to expand access to information and support equitable development for all levels of society. This is important to ensure prosperity, welfare, and social justice for the people. The transformation of mass communication in the digital era demands good, appropriate, and useful policies and regulations. One of the important policies is the change from Analog TV broadcasting to Digital TV in accordance with Law Number 11 of 2020 concerning Job Creation. This change reflects a significant transformation in the world of broadcasting, following the development of information and communication technology. Digitalization has changed the way information is delivered, received, and consumed, having a major impact on mass communication practices. This transformation opens up new opportunities but also presents great challenges, especially in the outermost, remote, and frontier (3T) regions. Equal Access to Information and Communication (PARI) is a priority in this policy. Although the internet has become part of human rights, there are still villages that have not yet been reached by broadband internet. Low internet speeds are a major problem. The process of switching from Analog to Digital TV aims to optimize limited frequencies, improve broadcast quality, and ensure interference-resistant broadcast stability. For this reason, further investment in digital infrastructure is needed, especially in the 3T region.